2020
DOI: 10.18231/2394-4994.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic applicability of simplified acute physiology score (saps 3) in critically ill adult surgical patients in a tertiary Indian hospital: A preliminary study

Abstract: Introduction and Aims: Prognostic indices are infrequently practiced in surgical intensive care units (SICU) of Indian tertiary care hospitals to assess the overall outcomes. Simplified Acute Physiology Score 3 (SAPS 3) prognostic system is now practiced globally and comprises easily measurable parameters on admission of patient in intensive care unit (ICU).The objective of the present study was to evaluate SAPS 3 index as a predictor of mortality in postoperative critically ill surgical patients admitted to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…10,17,21 The mean ICU (17.5 days) and hospital stay (25.7 days) are above the means demonstrated in other ICU studies or those demonstrated by Epimed Monitor ® for public national ICUs. 14,17,18 The main cause of hospitalization was infectious causes, especially respiratory infections that represented almost one third of the sample, being also the cause with the highest mortality (84%). The double risk of death of patients from the wards/emergency room in relation to those coming from the operating room points to a considerable relevance of origin in the outcome of the patients, a fact that is taken into account in the calculation of the prognostic score chosen for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17,21 The mean ICU (17.5 days) and hospital stay (25.7 days) are above the means demonstrated in other ICU studies or those demonstrated by Epimed Monitor ® for public national ICUs. 14,17,18 The main cause of hospitalization was infectious causes, especially respiratory infections that represented almost one third of the sample, being also the cause with the highest mortality (84%). The double risk of death of patients from the wards/emergency room in relation to those coming from the operating room points to a considerable relevance of origin in the outcome of the patients, a fact that is taken into account in the calculation of the prognostic score chosen for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the data needed to calculate index are mandatorily collected to compose a database of clinical and epidemiological databases as recommended by the Brazilian National Health Surveillance Agency (Agência Nacional de Vigilância Sanitária, abbreviated ANVISA) and the Brazilian Association of Intensive Care Medicine (Associação de Medicina Intensiva Brasileira, abbreviated AMIB). 3,5,6,[10][11][12][13][14][15][16][17][18][19] Adjusted mortality rates based on mortality predictions provided by prognostic scores have been increasingly used to assess the quality of care provided by different services. In countries such as the UK, Australia and New Zealand, successful database projects have contributed to improving the quality of care.…”
Section: Introductionmentioning
confidence: 99%